Digital Health Tracking and Health Literacy - Geroğlu, Berk (Turkey Health Literacy Journal, 2022)
Digital health is expressed as a general umbrella term for the use of information and communication technologies in health-relatedservices and processes (tele medicine, telehealth, telepharmacy, mobile health, etc.). Many concepts such as artificial intelligence, mobile applications and wearable technologies can also be considered in digital health.The World Health Organization (WHO) is harnessing the power of digital technologies and health innovation to accelerate global attainmentof health and the well-being.WHO Turkey Country Office Refugee Health Programme together with its main partner, Ministry of Health of Türkiye conduct some digitalhealth pilot applications to increase health literacy among refugees.